Given the point (2,3) and ( 0,6)

Let the point A be ( 2,3) and the point B be (0,6)

Now we know that the formula for the distance between two points is given as follows:

l AB l = sqrt[( xB-x)62 + (yB-yA)^2 ]

Then lest us substitue:

l AB l = sqrt[ (0-2)^2 + (6-3)^2]

= sqrt[(2^2) + (3^2)]

= sqrt( 4+ 9)

= sqrt(13)

**Then the distance between the point (2,3) and the point (0,6) is sqrt13 units>**

The distance d between the points (x1,y1) and (x2, y2) is given by:

d = sqrt{((x2-x1)^2 +(y2-y1)^2}.

Therefore the distance between the points (2,3) and (0,6) is given by substituting the x and y coordinates in the above formula in order.

Therefore d = sqrt {(0-2)^2+(6-3)^2}.

d = sqrt{2^2+3^2}.

d = sqrt{4+9}.

d = sqrt(13).

Therefore the distance between the points (2,3) and (0, 6) is sqrt13.

The distance between 2 points is the lengths of the segment that joins the 2 points.

We'll note the points: (2, 3) and (0, 6)

We'll write the formula of the distance:

[AB] = sqrt[(x2-x1)^2 + (y2-y1)^2]

We'll substitute the coordinates into the formula:

[AB] = sqrt[(0-2)^2 + (6-3)^2]

[AB] = sqrt (4 + 9)

[AB] = sqrt 13 units

**The distance between the given points A(2, 3) and B(0, 6) is sqrt 13 units.**